Human papillomavirus DNA detection in fine‐needle aspirates as indicator of human papillomavirus–positive oropharyngeal squamous cell carcinoma: A prospective study. Issue 3 (29th November 2016) - Sivars, Lars; Landin, David; Haeggblom, Linnea; Tertipis, Nikolaos; Grün, Nathalie; Bersani, Cinzia; Marklund, Linda; Ghaderi, Mehran; Näsman, Anders; Ramqvist, Torbjörn; Nordfors, Cecilia; Munck–Wikland, Eva; et al.
Abstract: Background: Human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (SCC) has a better outcome than most head neck squamous cell carcinomas (HNSCCs) and an HPV‐positive lymph node metastasis likely has an HPV‐positive oropharyngeal SCC origin. Determining HPV‐status in cervical lymph nodes by fine‐needle aspiration cytology (FNAC) may be useful for diagnosis. Methods: FNACs from 66 patients with neck masses were prospectively examined for HPV DNA and HPV16 mRNA by a polymerase chain reaction (PCR)‐based assay, and the data correlated to diagnosis and HPV‐status obtained from histopathological specimens. Results: Aspirates from 17 of 66 patients, later diagnosed with HPV‐positive oropharyngeal SCC, were HPV16 DNA‐positive. HPV16 mRNA was detected in all cases with extractable RNA. All remaining FNACs, including 18 branchial cleft cysts, were HPV DNA‐negative. HPV DNA status in the aspirates showed perfect concordance with corresponding biopsies. Conclusion: HPV16 DNA detection in fine‐needle aspirations from neck masses is reliable and HPV16 DNA in a metastasis is a strong indicator of an HPV‐positive oropharyngeal SCC. © 2016 Wiley Periodicals, Inc. Head Neck 39: 419–426, 2017